Dynamic Analysis of a Three-Species Food Chain System with Intra-Specific Competition - Guin, Lakshmi Narayan; Roy, Debdeep; Djilali, Salih (Journal of Environmental Accounting and Management, 2026)
The present article deals with a state of phase transition from stability to chaos emanated from a three-species food chain model with intra-specific competition. The model takes into account two distinct categories of functional response specifically Holling type II and Beddington-DeAngelis type along with the intra-specific competition among predators as well. The existence of equilibria having ecological feasibility together with stability in their proximity is addressed meticulously for the system. The perception of dissipativeness of the system in the realm of ecological principles is not ruled out however from the present investigation. Following the standard stability analysis, both the local and the global response of the co-existence equilibrium are paid due attention in order to understand the dynamics of the system. The fact that the proposed system experiences Hopf-bifurcation and chaos is note-worthy. Finally, the validity of the analytical results is established through numerical simulation based on model parameter values.